The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41419-021-04162-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective degradation of AR-V7 to overcome castration resistance of prostate cancer

Abstract: Androgen receptor splice variant 7 (AR-V7), a form of ligand-independent and constitutively activating variant of androgen receptor (AR), is considered as the key driver to initiate castration-resistant prostate cancer (CRPC). Because AR-V7 lacks ligand-binding domain, the AR-targeted therapies that aim to inactivate AR signaling through disrupting the interaction between AR and androgen are limited in CRPC. Thus, the emergence of AR-V7 has become the greatest challenge for treating CRPC. Targeting protein deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…Flow cytometry analysis was performed as previously reported [ 55 ]. Apoptotic cells were assessed using FITC Annexin V Apoptosis Detection kit (Cat.…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry analysis was performed as previously reported [ 55 ]. Apoptotic cells were assessed using FITC Annexin V Apoptosis Detection kit (Cat.…”
Section: Methodsmentioning
confidence: 99%
“…Nobiletin is a plant flavonoid extracted from citrus peels and possesses broad anti-cancer activity ( 128 , 129 ). A recent study showed that Nobiletin moderately reduced AR-V7 protein level in 22RV-1 cells at 20 ÎźM concentration and synergistically suppressed (at 40 mg/kg/2day) 22RV1 cell-derived xenograft tumor growth with Enzalutamide (20 mg/kg/2day) ( 53 ). The mechanistic study revealed that Nobiletin disrupted AR-V7 interaction with two deubiquitinases, USP14 and USP22, leading to proteasome-based AR-V7 degradation ( 53 ).…”
Section: Ar Protein Elimination Approaches In Preclinical Development...mentioning
confidence: 99%
“…Nobiletin is a natural product extracted from the peel and belongs to the polymethoxyflavonoids ( 72 ).Nobiletin mediates proteasomal degradation of AR-V7 by promoting ubiquitination of AR-V7 protein in CRPC cells ( 72 ). USP22 acts as a deubiquitinating enzyme that regulates the stability of AR-V7 protein.…”
Section: Resistance Mechanism Of Usp22mentioning
confidence: 99%